Absorption and sinking speed of the strand from bark of Terap (Artocarpus elasticus) - Fatmasari Isra; Nofrizal '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
An experiment to test of absorption and sinking speed of strand from bark of Terap (Artocarpus elasticus) was conducted to find the material of fishing gear’s construction. Bark of laticiferous were dried under sun light and spun to be a strand. The strand was tested their water absorption capacity and sinking speed in sea water into tube. The result show that the absorption capacity of the strand was reached 255.56% and sinking speed was 4.3 cm/sec. The relationship between absorption capacity, sinking speed and feasibility of strand from bark of laticiferous is detail discussed in this paper.Keyword: Absorption, fishing gear, terap (Artocarpus elasticus), sinking speed, strand